Franchising, business networks, concurrence, vertical restraints - Mayorga Toledano, María Cruz (CUADERNOS DE DERECHO TRANSNACIONAL, 2025)
Franchising agreements create a distribution network that requires a certain degree of coordination between the members and a market positioning, both generating potential restrictions on free competition. Specific European legislation establishes the conditions and limits within which these networks can operate legally. To this end, the new European legal framework introduces some necessary changes, which slightly modify the previous regulation, but it remains largely in line with what was previously regulated. The aim of this paper is to analyze and assess the current antitrust regulation of the franchise network as established by the new European legal environment, and to evaluate the main changes that have occurred as a result of the aforementioned regulation concerning the implementation and operation of that distribution network. Both the CJEU‘s analysis of the new regulation and that of national competition authorities will be taken into account. Furthermore, within the European framework, this task is complemented by considerations regarding the role played by Private International Law, as an essential element given the distinctly international nature of franchise networks. A review of the sources of international franchise contracts is therefore necessary due to the potential interference with EU competition law.